Thinking Outside the 'Murder Box': Virtual Violence and Pro-social Action in Video Games. (24th December 2018) - Denham, Jack; Spokes, Matthew
Abstract: The 'murder box' is a virtual, lawless space where anything goes. According to Atkinson and Rodgers, when debauched and hedonistic experiences are combed-out of our everyday lives as society ascends a gradual arc of civility, voyeuristic, pleasure-seekers can live out their violent, sadistic fantasies. Atkinson and Rodgers apply this popular criminological metanarrative, rooted in Freud, Elias and Presdee, to violence in gaming. In the context of their game of choice (Grand Theft Auto V), we empirically test the idea that given limitless avenues for violence, people will necessarily act out violent desires. We find that player choices are mixed, considered and vary wildly from untamed subjective violence, to more pro-social behaviours. Our contribution is to argue for a more measured understanding of player–game interaction that accounts for the broader spectrum of Elias' work, including those internalized self-controls directing individuals away from hedonistic decisions. At the same time, this contribution should be read as a response to the often absolutist theoretical positions adopted in cultural criminology more broadly that require closer empirical scrutiny.